X-Men origins. Wolverine [videorecording (Blu-Ray)] - Jackman, Hugh; Benioff, David; Woods, Skip; Hood, Gavin; Schreiber, Liev; Huston, Danny, 1962-; Monaghan, Dominic, 1976-; Reynolds, Ryan; Gregson-Williams, Harry (20th Century Fox Home Entertainment, 2009)
Somewhere in the wilds of northwest Canada in the early 1800s, Logan and Victor, two half-brothers with special powers grow up amid violence. Eventually they will become the near-indestructible warriors known as Wolverine and Sabretooth. William Stryker is a sinister government operative whose Weapon X program experiments keep pulling Wolverine back in. Kayla Silverfox shares a peaceful Canadian co-existence with Wolverine as he tries to drop out of the program. Along the way, Wolverine encounters many mutants, both familiar and new.